The Reed-Stanton press rig for the generation of reproducible fingermarks: Towards a standardised methodology for fingermark research. Issue 1 (January 2016) - Reed, H.; Stanton, A.; Wheat, J.; Kelley, J.; Davis, L.; Rao, W.; Smith, A.; Owen, D.; Francese, S.
Abstract: In the search for better or new methods/techniques to visualise fingermarks or to analyse them exploiting their chemical content, fingermarks inter-variability may hinder the assessment of the method effectiveness. Variability is due to changes in the chemical composition of the fingermarks between different donors and within the same donor, as well as to differential contact time, pressure and angle. When validating a method or comparing it with existing ones, it is not always possible to account for this type of variability. One way to compensate for these issues is to employ, in the early stages of the method development, a device generating reproducible fingermarks. Here the authors present their take on such device, as well as quantitatively describing its performance and benefits against the manual production of marks. Finally a short application is illustrated for the use of this device, at the method developmental stages, in an emerging area of fingerprinting research concerning the retrieval of chemical intelligence from fingermarks. Graphical abstract: Highlights: An alternative design for a fingerprint rig generator is proposed. In this rig pressure angle and contact time can be selected naturally increasing reproducibility. A novel image processing enables quicker and quantitative quality control of the prints generated. The fingerprint rig is useful in the development of a MALDI MSI strategy for fingermark dating.